Protocol for isolating the single bacteriocyte from whiteflies for single-cell RNA-seq analysis - Na-Na Li; Hui Quan; Jun-Bo Luan (STAR Protocols)
Summary: Bacteriocytes are specialized insect cells adapted to harbor symbionts. However, their low number in individual whiteflies makes obtaining enough for transcriptome sequencing challenging. Here, we present a protocol for the isolation of whitefly bacteriocytes. We describe steps for preparing the single bacteriocyte sample, cDNA amplification library construction, sequencing, and data analysis. Our protocol offers convenience and efficiency for conducting single-cell sequencing for bacteriocytes and has the potential to be applied to other insect cells.For complete details on the use and execution of this protocol, please refer to Li et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.